Rural finance, development and livelihoods in China - Heather Xiaoquan Zhang; Nicholas Loubere (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2013)
Establishing an inclusive financial system with comprehensive and accessible services in rural areas is increasingly promoted as a crucial element for socio-economic development both in China and globally. Yet, in existing research on China's agricultural and rural development, relatively less attention has been paid to the ways in which changes in the provision of rural finance have impacted the livelihoods of individuals, families and communities from the perspectives of local people. This paper intends to contribute to our understanding of the relationship between rural finance and development by delineating a recent history of financial service extension to rural areas since the founding of the People's Republic of China in 1949. We analyse, in particular, the accelerated pace of the expansion and diversification of such services together with a deeper penetration of the so-called 'microfinance industry' in rural China since the mid-2000s. We analyse the major actors and dynamics involved, the strengths and weaknesses in current scholarship, and suggest ways forward in order to deepen our understanding of the relationship between rural finance, development and the livelihoods in China and beyond.
Keywords: 330; rural financial services; financial extension and diversification; urban-rural integration; microcredit; livelihoods; China